Thermomechanical waves in magnetized microelongated thermoelastic medium using the Moore–Gipson–Thompson model - Mohamed I. Hilal; Ramadan Tantawi; Ibrahim S. Elshazly; Imed Bachar; Saurav Sharma; Khaled Lotfy (AIP Advances)
This study addresses two-dimensional wave propagation in a microelongated thermoelastic medium subjected to an initial magnetic field, utilizing the Moore–Gibson–Thompson (M–G–T) model. The medium is initially stressed under constant pressure and influenced by gravity. An analytical solution is derived using the harmonic wave approach to obtain expressions for stress, strain, and temperature. These expressions are graphically represented alongside a numerical scheme for aluminum-epoxy to validate the analytical results. The wave number and other physical effects used significantly impact the variation of the field quantities.